THE ROLE OF STRATEGIC IMPROVISATION AND STRATEGIC LEADERSHIP IN STIMULATING DISTINGUISHED ORGANIZATIONAL PERFORMANCE AN ANALYTICAL STUDY OF ADMINISTRATIVE LEADERS AT THE TECHNICAL INSTITUTE / BABYLON - Jwan Fadel Mahdi (Scholar Express Journals, 2023)
The current research adopts the study of strategic improvisation and strategic leadership in its dimensions as an independent variable and its role in stimulating distinguished organizational performance. The research seeks to achieve a goal represented by testing the relationship between the two variables, and the impact of one on the other, to achieve this goal, a hypothetical model was built that defines the relationship between the two variables, and several main and sub-hypotheses emerged from it. The Technical Institute / Babylon was selected as a community for research and testing its hypotheses. Due to the large size of the original sample, the research sample consisted of (90) teachers who hold administrative positions in the researched organization with a random sample of the teachers of the researched organization. To verify the validity of the hypotheses that were built, as well as the treatment of the data on which the answers of the research sample were based, the statistical program (SPSS) was used, and the selection of appropriate statistical methods that are consistent with the nature of the research, The results of the study showed the existence of a significant correlation and influence between strategic improvisation and strategic leadership at the macro level of the responding sample by stimulating the distinguished organizational performance. The research reached a set of recommendations based on the research results. Finally, the research presented some proposals
Keywords: strategic leadership; organizational performance